Answer:
a) -2
b) y = -2x + 6
Explanation:
Question (a)
Point A = (-1, -2)
Point B = (7, 2)
![\sf gradient\:of\:AB=(change\:in\:y)/(change\:in\:x)=(2-(-2))/(7-(-1))=(4)/(8)=\frac12](https://img.qammunity.org/2023/formulas/mathematics/high-school/p4523lpv58bdyol8vw7qk7vqdofiadr4ir.png)
If lines are perpendicular to each other, the product of their gradients will be -1.
Let g be the gradient of the perpendicular line:
![\implies \sf \frac12 * g=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/gxeiab6xp3o2cjbgr6mml0zrsy9yqrbwst.png)
![\implies \sf g=-1 / \frac12=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/deiukr3qle1zgctvjrvm7fkd5pq2xkugyt.png)
Therefore, the gradient of the line perpendicular to AB is -2
---------------------------------------------------------------------------------------------
Question (b)
![\sf midpoint\:of\:line = \left((x_1+x_2)/(2),(y_1+y_2)/(2)\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/i74exuiky6s4gkw26r5kdx435j5cpuoig2.png)
![\sf let\:point\:A=(x_1,y_1)=(-1,-2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/wekqc239rr57t2vpgznjc5tlh7nergk9ja.png)
![\sf let\:point\:B=(x_2,y_2)=(7,2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/2h61o3osiz4mgl5el4an6yki9r3s2qvk84.png)
![\sf \implies midpoint\:of\:line\:AB = \left((-1+7)/(2),(-2+2)/(2)\right)=(3,0)](https://img.qammunity.org/2023/formulas/mathematics/high-school/5erzr3jl5relik56g833q0a15x5iaoldos.png)
We now know the gradient and a point on the perpendicular line.
So we can use the point-slope form of a linear equation:
![\sf y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ctsq07qn11noz3tjx3mq8trdednhpgvlsx.png)
![\implies \sf y-0=-2(x-3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/odobfu09uqmi0tu2eqhtm3y6ex97fl0nfh.png)
![\implies \sf y=-2x+6](https://img.qammunity.org/2023/formulas/mathematics/high-school/ybru7mhxb8mf3l8jl30s9fpphg2qc723et.png)